Legal study on media ownership law in Malaysia with specific reference to the Australian legal position / Emmy Nabilah Ismail Hashim ... [et al.] - Ismail Hashim, Emmy Nabilah; Abdul Kadir, Noor Ashikin; Ab Wahab, Siti Norfadila; Freddy, Sandra Ynette (Faculty of Law, 2013)
This is study on Media Ownership Regulations in the Communication and Multimedia Act (CMA) 1998 and other statutes which is completed as a fulfillment of the study of the Bachelor of Legal Studies (Hons). The study concerns mainly in the media ownership of the numerous media stations in Malaysia and its impact on democracy and economy. The research is done on the basis of the national objectives under the CMA 1998 which calls for establishing Malaysia as a major global centre and also the hub for communications, multimedia information and content services. This research addressed the issue of the current media ownership in Malaysia being highly concentrated ia the hands of a few and it is linked to political parties. This may endanger the democracy of people and media information may be influence by certain political views. The objective of this research is to study the existing laws in Malaysia (CMA 1998) and other statutes in regulating media ownership and the effects of politically-influenced media to the mindsets of the public, to study the media ownership regulations in Australia for comparative analysis and to give recommendations on how to solve the problem of media ownership that influences the political views of the public. This research discovers that the structure of media ownership regulations are not suitable to be adapted into the Malaysian media industry due to factors such as the size of the market and lack of media players. Thus, recommendations are given to improve the situation of the current media in Malaysia as an alternative to the structure of media ownership regulations.